Resource mobilization service at the General Hospital of Tien Giang Center, Vietnam: The demands of in-patients with diabetes and cardiovascular disease - Vu Thu Trang; Nguyen Hanh Dung; Tran Ngoc Yen; Nguyen Thi Phuong; Pham Tien Nam (Social Work & Society, 2024)
Studies on the demands of resource mobilization service among in-patients with diabetes and cardiovascular disease remain limited. This study aimed to estimate the demands of resource mobilization service and to examine several associated factors among in-patients with diabetes and cardiovascular disease at the General Hospital of Tien Giang Center, Vietnam. This was a cross-sectional study conducted on 196 in-patients, of which 98 were in-patients with diabetes disease and 98 were in-patients with cardiovascular disease. Additionally, this study used 8 in-depth interviews to collect data. The study results showed that in-patients with diabetes and cardiovascular disease had a high demand for resource mobilization services (over 90%). In the univariate regression models, significant factors for the demands of resource mobilization service among in-patients with cardiovascular disease were living area, marital status, economic condition, and the number of treatments. We did not find a statistically significant association with the resource mobilization demands of diabetic in-patients. The study provided recommendations to stakeholders to promote resource mobilization services for diabetic and cardiovascular in-patients in difficult circumstances. These findings had important implications for future research on factors associated with resource mobilization services among in-patients with diabetes and cardiovascular disease.